Functionalization of soft materials for cardiac repair and regeneration. (19th May 2019) - Kuraitis, Drew; Hosoyama, Katsuhiro; Blackburn, Nick J. R.; Deng, Chao; Zhong, Zhiyuan; Suuronen, Erik J.
Abstract: Coronary artery disease is a leading cause of death in developed nations. As the disease progresses, myocardial infarction can occur leaving areas of dead tissue in the heart. To compensate, the body initiates its own repair/regenerative response in an attempt to restore function to the heart. These efforts serve as inspiration to researchers who attempt to capitalize on the natural regenerative processes to further augment repair. Thus far, researchers are exploiting these repair mechanisms in the functionalization of soft materials using a variety of growth factor-, ligand- and peptide-incorporating approaches. The goal of functionalizing soft materials is to best promote and direct the regenerative responses that are needed to restore the heart. This review summarizes the opportunities for the use of functionalized soft materials for cardiac repair and regeneration, and some of the different strategies being developed.